Analisa Dan Optimasi Pada Teknologi Jaringan Wireless Pada Ruangan Laboratorium Dan Kantor Gedung Mangudu Universitas Telkom Menggunakan Wireless Site Survey - Hasrinaldi Hasniman Harun; Umar Yunan K.S.H; M. Teguh Kurniawan (LPPM STIKOM Tunas Bangsa, 2023)
The Mangudu Building is a facility at Telkom University designed to accommodate the university's industrial engineering department, primarily for the needs of introducing manufacturing production. The building is equipped with an internal network to accommodate internet access. However, the building is relatively old and has been left in its current state. The networking equipment in use can also be considered outdated. Therefore, a reevaluation is necessary to determine the extent of wireless network implementation and to identify network issues in the building. The condition of the wireless network in the Mangudu Building yields results indicating that the signal strength emitted by the Cisco Aironet 1700i access point on the first-floor receive a less favorable indicator value as their signal strength is above -60 dBm. Therefore, the author proposes replacing the access point with the Ruijie RG-AP880-AR and adding a second access point. The proposed changes result in the majority of rooms on both the first and second floors having a very good indicator value, with readings below -50 dBm for both the 2.4 GHz and 5 GHz frequencies